INTEGRATION OF MEDIA DIDACTICS INTO THE EDUCATIONAL SPACE OF THE NEW UKRAINIAN SCHOOL - Chervinska, Inna; Fomin, Kateryna; Nykorak, Yaroslav; Chervinskyi, Andrii (Mountain School of Ukrainian Carpaty, 2021)
The article presents the most effective ways of integrating media didactics into the educational space of the New Ukrainian School with the help of innovative media technologies and media resources. The authors emphasize the fact that in modern realities the key role is played by the ability to work with different types of media texts, assess the quality and reliability of the information received, resist manipulative influence, to form constructive media behavior. Researchers emphasize the opinion that media didactics explores the functioning of the media in the learning process, and the purpose of media education is to prepare youth for the critical perception of media resources. It is specified that modern Pedagogy considers media education technologies as one of the effective means of improving the quality of education, as media educational technologies embody the principles of humanization of education, contributing to improving the intellectual, cultural, spiritual, moral level of future citizens. It is emphasized that the idea of integrative education reflects one of the main concepts of development of the New Ukrainian school - the idea of forming a competent personality and the development of students' holistic vision of the world. Researchers point to the importance of integrativeness in modern education, which aims to realize the integrity of the educational process as an important means of socializing a growing personality. Prospects for the integration of the pedagogical potential of media resources and media technologies of media didactics in the educational process of the New Ukrainian School are outlined. Because media didactics plays an important role in modernizing the content of education and gives it an innovative character.